Pelaksanaan Penyuluhan Sampah Desa Tamasaju, Kecamatan Galesong Utara, Kabupaten Takalar 2022 - Istiqamah Nurul Fajriah; Handayani Meliana; Jayadilaga Yadi (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
Humans in fulfilling their daily needs will emit waste products in the form of waste, starting from organic waste and also anorganic waste. The waste must be placed and processed properly so that it can be reused and processed properly so that no one is harmed by the waste. The purpose of this service is to overcome the problem of waste in Tamasaju Village, North Galesong District, Takalar Regency which is the main problem in the area.  The method used consisted of physical interventions (making demonstration trash cans) and non-physical (providing counseling). This activity was carried out in Tamasaju Village with 28 residents involved. Data analysis used SPSS 20 by comparing the pre-test and post-test values ​​of the respondents. The results of data analysis showed that there was an increase in the average knowledge of 28 respondents before counseling (51.4%) with high knowledge after evaluating counseling on the importance of disposing of waste in its place (84.67%).